Dust removal characteristics of a supersonic antigravity siphon atomization nozzle. (December 2020) - Zhang, Tian; Jing, Deji; Ge, Shaocheng; Wang, Jiren; Chen, Xi; Ren, ShuaiShuai
To improve the trapping efficiency of respiratory dust by aerodynamic atomization, reduce the energy consumption and the requirements for the working conditions of nozzles and maintain the health and safety of workers, a comparative experiment evaluating aerodynamic atomization dust removal characteristics was conducted with a self-developed supersonic siphon atomization nozzle, which utilizes a Laval nozzle as the core, and an existing ultrasonic atomization nozzle. The experimental results showed that the new type of nozzle, from the perspectives of droplet speed, conservation of water and pressure, range, and attenuation view, completely surpasses the traditional pneumatic atomization nozzle. A supersonic antigravity siphon atomizer produces a cloud fog curtain composed of high-speed droplets and high-speed air. The particle size of the droplets is less than 10 µ. At the same flow rate of water, its dust removal rate is twice as high as that of ultrasonic nozzles. When the dust removal efficiency is the same, the water consumption of the supersonic siphon atomizer nozzle is 1/2, the air flow rate is 1/3, and the power consumption is 1/2 that of the ultrasonic atomizing nozzles. Siphon atomization can siphon at a total air pressure of 0.2 MPa, and the siphon pressure can reach 0.03 MPa at a total air pressure of 0.4 MPa, which increases with the increase in total inlet air pressure. For the first time, the process of siphoning and nozzle internal atomizing in the field of supersonic atomization dust removal is truly realized. The ultrafine sized droplets with high speeds produced by the new nozzle allow them to cover the limited working space in a shorter time, have a more effective trapping effect for a large number of fine dust particles, and quickly suppress the dust with greater kinetic energy. Therefore, the requirements for the working conditions are reduced, which will save more energy compared to the currently used nozzles available on the market.